Rates of Depression and Post-Traumatic Stress Disorder Differ by Insurance Type in Chronic Ankle Instability Patient - John R. Allen BS; Caroline Hoch BS; Joshua L. Morningstar BS; Daniel Scott MD; Christopher E. Gross MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle; Other Introduction/Purpose: Chronic ankle instability (CAI) is one of the most commonly encountered clinical problems by orthopaedic foot and ankle surgeons, however, little research exists on the impact of insurance status on the incidence and outcomes of CAI. This study aims to investigate the association between psychiatric diagnosis and insurance status in CAI patients to determine if insurance subgroups differ in rate of surgery and postoperative success, as well as identify if psychiatric diagnoses are more common within certain insurance types. Methods: A retrospective review was conducted of 276 patients (280 ankles) treated between 2005 and 2021 at an academic medical center by one of three fellowship-trained foot and ankle orthopaedic surgeons, of which 56 (20.0%) underwent surgery, seven (2.5%) underwent reoperation, and 130 (46.4%) had a concomitant psychiatric diagnosis (i.e., anxiety=111, depression=105, post-traumatic stress disorder [PTSD]=19, obsessive-compulsive disorder [OCD]=6, bipolar disorder [BPD]=5). Insurance type was categorized as privately- (n=147) or government-funded (n=121). For further analysis, the government-funded cohort was broken into the following groups: Medicare (n=77), Veterans Affairs (n=20), Worker’s Compensation (n=18), and Medicaid (n=6). Eleven patients (12 feet) were uninsured. Data collected included demographics, conservative and operative treatments, patient- reported outcome measures (PROMs) (e.g., Foot and Ankle Ability Measure [FAAM]), and reoperation rate. Results: When examining binomial insurance groups, rate of surgery (private=15.6%, government=24.8%; p=.061) approached, but did not reach, significance and reoperation rate (private=17.4%, government=10.0%; p=.451) did not differ. Postoperatively, PROMs did not differ between private and government insurance types, but FAAM Physical Function (p=.046) and Total (p=.035) scores were best with Medicare insurance when analyzing all insurance groups. Instance of mental illness (p=.111) or certain psychiatric diagnoses did not differ between privately- and government-insured patients, but depression (p=.013) and PTSD (p=.050) were significantly less common among patients with Veterans Affairs insurance. Conclusion: CAI patients were not found to have differing need for surgery between insurance types. This was similar for postoperative success, aside from Medicare patients having better reported FAAM scores. Furthermore, patients with a psychiatric diagnosis were not more common to an insurance group, but specific depression and PTSD diagnoses were least common for Veterans Affairs patients.